The efficacy and safety of glecaprevir plus pibrentasvir in 141 patients with severe renal impairment: a prospective, multicenter study. Issue 9 (14th March 2019) - Atsukawa, Masanori; Tsubota, Akihito; Toyoda, Hidenori; Takaguchi, Koichi; Nakamuta, Makoto; Watanabe, Tsunamasa; Michitaka, Kojiro; Ikegami, Tadashi; Nozaki, Akito; Uojima, Haruki; Fukunishi, Shinya; Genda, Takuya; et al.
Summary: Background: Patients with chronic hepatitis C are often complicated by chronic kidney disease (CKD). Aim: To evaluate the efficacy, safety and pharmacokinetics of glecaprevir/pibrentasvir in patients with severe renal impairment. Methods: In a prospective, multicentre study involving 35 medical institutions, 832 genotype 1‐3 patients were treated with glecaprevir/pibrentasvir. The efficacy and safety of glecaprevir/pibrentasvir were analysed for patients with CKD stage 4 or 5. Multivariate analysis was performed to identify the factors associated with the most frequently observed adverse event. In patients undergoing haemodialysis, a pharmacokinetic study was conducted to investigate the dialysability of the drugs: plasma samples were obtained from the arterial and venous sides of a dialyser to serially measure drug concentrations. Results: The subjects comprised 141 patients (32 with CKD stage 4 and 109 with CKD stage 5), of whom 100 were undergoing haemodialysis. All but one stage 5 CKD patients undergoing haemodialysis achieved sustained virologic response (99.3%). Adverse events were observed in 39.7% of subjects: pruritus was the most frequent (30.5%), and was significantly associated with haemodialysis. In the pharmacokinetic study, no arterial‐venous differences in the plasma concentrations of glecaprevir/pibrentasvir were detected during the haemodialysis sessions. Conclusions: Glecaprevir/pibrentasvir was highly effective and safe in chronic hepatitis C patients with severe renal impairment. Haemodialysis was associated with increased incidence of pruritus, which was the most frequent adverse event, but had little or no influence on the drug concentrations, which indicated that their dialysability is very low and that no dose modification is required in patients undergoing haemodialysis. (UMIN registration no. 000032073).